Formation of Nanoporous Anodic Alumina by Anodization of Aluminum Films on Glass Substrates - Lebyedyeva, Tetyana (Springer US, 2016)
Our research was aimed at the study of aluminum films and porous anodic alumina (PAA) films in thin-film РАА/Al structures for optical sensors, based on metal-clad waveguides (MCWG). The results of the scanning electron microscopy (SEM) and atomic force microscopy (AFM) studies of the structure of Al films, deposited by DC magnetron sputtering, and of PAA films, formed on them, are presented in this work.